Risk Management-Driven Policy Rate Gap - Giovanni Caggiano; Efrem Castelnuovo; Gabriela Nodari (Center for Economic Studies and ifo Institute (CESifo), 2018)
We employ real-time data available to the US monetary policy makers to estimate a Taylor rule augmented with a measure of financial uncertainty over the period 1969-2008. We find evidence in favor of a systematic response to financial uncertainty over and above that to expected inflation, output gap, and output growth. However, this evidence regards the Greenspan-Bernanke period only. Focusing on this period, the “risk-management” approach is found to be responsible for monetary policy easings for up to 75 basis points of the federal funds rate.
Keywords: C20; E40; E50; 330; risk management-driven policy rate gap; uncertainty; monetary policy; Taylor rules; real-time data